Shifts in macroalgae composition alters carbon flow in Coastal Baltic Sea ecosystems: implications for dissolved organic carbon bioavailability and flux - Hall, Jack R.; Herkül, Kristjan; Baltar, Federico; Hepburn, Christopher D.; Martin, Georg (Frontiers in Marine Science, 2024)
The extracellular release of dissolved organic carbon (DOC) from marine macroalgae supports coastal ecosystem function by supplying photosynthetically fixed carbon to higher trophic levels via the microbial loop. Despite its widely acknowledged biogeochemical importance, DOC is not typically included in primary production estimates of coastal systems. Additionally, little is known about how changes in species composition and coverage will affect the supply of DOC to coastal systems. Within the context of the Baltic Sea, anthropogenic forces are driving a decline in habitat forming kelp species (Fucus vesiculosus) which is superseded by filamentous/turfing algal species, a pattern of change observed globally in numerous other aquatic systems. To evaluate how the drivers of this change may impact the flow of carbon within the Baltic Sea coastal system, the production of DOC by the filamentous algae (Ectocarpus siliculosus) was examined and its rate of release determined (0.095 mg C • g DW -1 • h -1 in light and 0.070 mg C • g DW -1 • h -1 in dark). In addition, bioassays were used to assess the short-term DOC use by bacteria as a proxy of the lability of the released products, with the majority (28.7% released in light and 18.6% released in dark) of the products remaining after 120 hours. This data was linked with long term macroalgae biomass and coverage surveys in order to assess changes in macroalgae community structure through time and to produce standing stock estimates of F. vesiculosus. DOC production as a metric of algal coverage was used to make a preliminary estimation of how changes in community structure may impact the flow of carbon within the system. Our results suggest that decreased levels of DOC released by filamentous algae relative to F. vesiculosus will act to reduce microbial activity. Our model estimates the presence of approximately 150,000 tonnes of F. vesiculosus (dry weight) within the Estonian coastal system translating to an annual release of 7,391 tonnes of DOC. Our study indicates that filamentous-dominated systems have likely altered carbon flow, impacting the broader ecology of the Baltic Sea. Consequently, the loss of kelp species and the...